2009
DOI: 10.1038/sj.bjc.6605109
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic mutation in the pleckstrin homology domain of AKT1 in endometrial carcinomas

Abstract: BACKGROUND: The phosphatidylinositol 3 0 -kinase (PI3K) -AKT pathway is activated in many human cancers and plays a key role in cell proliferation and survival. A mutation (E17K) in the pleckstrin homology domain of the AKT1 results in constitutive AKT1 activation by means of localisation to the plasma membrane. The AKT1 (E17K) mutation has been reported in some tumour types (breast, colorectal, ovarian and lung cancers), and it is of interest which tumour types other than those possess the E17K mutation. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 29 publications
0
104
1
5
Order By: Relevance
“…Furthermore, recent evidence indicates that the molecular mechanism underlying activation of AKT1(E17K) is a broadened target lipid selectivity that allows high-affinity binding to PI(4,5)P2 (Landgraf et al, 2008). AKT1(E17K) mutation has been reported in various human cancers, including breast cancers, colorectal cancers, ovarian cancers, squamous cell carcinoma of the lung, endometrial carcinomas, urothelial carcinoma and bladder cancer, but not in other multiple human malignancies, including acute leukemias and liver cancers (Carpten et al, 2007;Kim et al, 2008;Mahmoud et al, 2008;Malanga et al, 2008;Mohamedali et al, 2008;Riener et al, 2008;Shoji et al, 2009;Zilberman et al, 2009;Askham et al, 2010). These studies suggested that AKT1(E17K) mutation occurs at a low frequency and in a tissue-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent evidence indicates that the molecular mechanism underlying activation of AKT1(E17K) is a broadened target lipid selectivity that allows high-affinity binding to PI(4,5)P2 (Landgraf et al, 2008). AKT1(E17K) mutation has been reported in various human cancers, including breast cancers, colorectal cancers, ovarian cancers, squamous cell carcinoma of the lung, endometrial carcinomas, urothelial carcinoma and bladder cancer, but not in other multiple human malignancies, including acute leukemias and liver cancers (Carpten et al, 2007;Kim et al, 2008;Mahmoud et al, 2008;Malanga et al, 2008;Mohamedali et al, 2008;Riener et al, 2008;Shoji et al, 2009;Zilberman et al, 2009;Askham et al, 2010). These studies suggested that AKT1(E17K) mutation occurs at a low frequency and in a tissue-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that AKT's effect in EC initiation and progression does not emerge from gain-of-function mutations but rather from the activation of upstream proteins. However, while the great majority of ECs display multiple mutations in the PI3K/PTEN/Akt pathway, mutation in Akt1 has been demonstrated to be sufficient for oncogenic transformation (Shoji et al 2009). …”
Section: Cancermentioning
confidence: 99%
“…We appreciate the attention given by Drs Dutt, Salvesen, Greulich, Sellers, Beroukhim and Meyerson to our recent publication 'The oncogenic mutation in the pleckstrin homology domain of AKT1 in endometrial carcinomas' (Shoji et al, 2009). In this article, we report a 2% mutational frequency of AKT1 (E17K) among 101 endometrial carcinomas.…”
Section: Sirmentioning
confidence: 79%